The relationship between BMI and blood pressure in school-age children in Izmir, Turkey. - Öztürk Haney, Meryem (Progress in Nutrition, 2018)
Objective: Prevalence of hypertension and obesity are increasing in children. This study aimed to determine the relationship between hypertension and obesity among school-age children in Izmir (western part of Turkey), which is the third largest city in Turkey. Design: Cross-sectional descriptive study. Participants: The sample consisted of 1289 students aged between 6 and 10 attending two primary schools in Izmir, a province in Turkey. Measurements: The students’ weights, heights and blood pressures were measured. Data Analysis: The independent sample t-test, anova test and multiple regression analysis were used for statistical analyses. Results: The prevalence of hypertension and obesity was 20.2% and 14.7% respectively. Gender was not associated with hypertension and obesity in children. The body mass index was statistically significant as an explanatory variable of hypertension for both genders. Conclusion: Overweight and obese children are at a significantly higher risk for hypertension than are normal weight children.